Breeze: an integrated quality control and data analysis application for high-throughput drug screening - Swapnil Potdar; Aleksandr Ianevski; John-Patrick Mpindi; Dmitrii Bychkov; Clément Fiere; Philipp Ianevski; Bhagwan Yadav; Krister Wennerberg; Tero Aittokallio; Olli Kallioniemi; Jani Saarela; Päivi Östling (OXFORD UNIV PRESS, 2022)
High-throughput screening (HTS) enables systematic testing of thousands of chemical compounds for potential use as investigational and therapeutic agents. HTS experiments are often conducted in multi-well plates that inherently bear technical and experimental sources of error. Thus, HTS data processing requires the use of robust quality control procedures before analysis and interpretation. Here, we have implemented an open-source analysis application, Breeze, an integrated quality control and data analysis application for HTS data. Furthermore, Breeze enables a reliable way to identify individual drug sensitivity and resistance patterns in cell lines or patient-derived samples for functional precision medicine applications. The Breeze application provides a complete solution for data quality assessment, dose-response curve fitting and quantification of the drug responses along with interactive visualization of the results.